A Sample of Seyfert-2 Galaxies with Ultraluminous Galaxy-wide Narrow-line Regions: Quasar Light Echoes? - Schirmer, M. (2013)
We report the discovery of Seyfert-2 galaxies in SDSS-DR8 with galaxy-wide, ultraluminous narrow-line regions (NLRs) at redshifts z = 0.2-0.6. With a space density of 4.4 Gpc–3 at z ~ 0.3, these "green beans" (GBs) are amongst the rarest objects in the universe. We are witnessing an exceptional and/or short-lived phenomenon in the life cycle of active galactic nuclei (AGNs). The main focus of this paper is on a detailed analysis of the GB prototype galaxy J2240–0927 (z = 0.326). Its NLR extends over 26 × 44 kpc and is surrounded by an extended NLR. With a total [O III] λ5008 luminosity of (5.7 ± 0.9) × 1043 erg s–1, this is one of the most luminous NLRs known around any type-2 galaxy. Using VLT/XSHOOTER, we show that the NLR is powered by an AGN, and we derive resolved extinction, density, and ionization maps. Gas kinematics is disturbed on a global scale, and high-velocity outflows are absent or faint. This NLR is unlike any other NLR or extended emission line region known. Spectroscopy with Gemini/GMOS reveals extended, high-luminosity [O III] emission also in other GBs. WISE 24 μm luminosities are 5-50 times lower than predicted by the [O III] fluxes, suggesting that the NLRs reflect earlier, very active quasar states that have strongly subsided in less than a galaxy's light-crossing time. These light echoes, or ionization echoes, are about 100 times more luminous than any other such echo known to date. X-ray data are needed for photoionization modeling and to verify the light echoes.